The fifth sense: Mechanosensory regulation of alpha-actinin-4 and its relevance for cancer metastasis. (November 2017) - Thomas, Dustin G.; Robinson, Douglas N.
Abstract: Metastatic cancer cells invading through dense tumor stroma experience internal and external forces that are sensed through a variety of mechanosensory proteins that drive adaptations for specific environments. Alpha-actinin-4 (ACTN4) is a member of the α-actinin family of actin crosslinking proteins that is upregulated in several types of cancers. It shares 86% protein similarity with α-actinin-1, another non-muscle ACTN isoform, which appears to have a more modest role, if any, in cancer progression. While they share regulatory mechanisms, such as phosphorylation, calcium binding, phosphatidyl inositol binding, and calpain cleavage, α-actinin-4 exhibits a unique mechanosensory regulation that α-actinin-1 does not. This behavior is mediated, at least in part, by each protein's actin-binding affinity as well as the catch-slip-bond behavior of the actin binding domains. We will discuss currently known modes of ACTN4 regulation, their interactions, and how mechanosensation may provide major therapeutic targeting potential for cancer metastasis.